Inovasi Pemasaran Jasa : Meningkatkan Daya Saing Bisnis di Era Digital - Brian Ramadhan; Maruf, Fachdika Neza; Fachri Darmawan; Kevin Aditya Santoso; Mitasari; Ade maulana; Djoko Hananto (Philosophiamundi, 2024)
Services marketing has become a key component in business strategy in the ever-growing digital era. The digital era has brought fundamental changes in the way companies promote, deliver and manage their services. Service marketing innovation is becoming increasingly important in this context, because companies that are able to adapt and utilize technology and digital trends can increase their competitiveness in an increasingly competitiveÂ market. In this context, in-depth research and understanding of service marketing innovation is crucial. This article will explain the important role of service marketing innovation in increasing business competitiveness in the digital era. We will explain various innovation strategies that can be implemented, case studies of company success in implementing this innovation, as well as its impact on business growth and customerÂ satisfaction.